The Ross Procedure in Children with Congenital Heart Disease - Nabil Dib; Nancy Poirier; Ismail Bouhout; Paul Khairy (Journal of Cardiovascular Development and Disease)
Aortic valve disease accounts for approximately 5% of all congenital heart defects in children. Choosing the optimal valve replacement in this population is challenging, as it must ensure durability, accommodate growth, and minimize the need for long-term anticoagulation. Biological valves do not require anticoagulation but lack durability and growth potential, leading to frequent reoperations. Mechanical valves offer longevity but necessitate lifelong anticoagulation and do not grow with the child. Among the available surgical options, the Ross procedure has emerged as a preferred approach due to its favorable hemodynamic performance, growth potential, and freedom from anticoagulation. First described in 1967, this technique involves replacing the diseased aortic valve with a pulmonary autograft and reconstructing the right ventricular outflow tract using a human or non-human valve substitute. Despite its advantages, the procedure is technically demanding, has a considerable learning curve, and transforms a single-valve pathology into a bivalvular condition. This narrative review provides an updated perspective on the Ross procedure in children, focusing on long-term survival, reoperation rates, and the role of percutaneous valve replacement in delaying surgical reintervention. By synthesizing the latest evidence, we aim to clarify the current standing of the Ross procedure as a durable and effective solution for pediatric aortic valve disease.